Fabrication of Intragastric Floating, Controlled Release 3D Printed Theophylline Tablets Using Hot-Melt Extrusion and Fused Deposition Modeling - Bhupendra Raj Giri; Eon Soo Song; Jaewook Kwon; Ju-Hyun Lee; Jun-Bom Park; Dong Wuk Kim (MDPI AG, 2020)
This work presents a novel approach for producing gastro-retentive floating tablets (GRFT) by coupling hot-melt extrusion (HME) and fused deposition three-dimensional printing (3DP). Filaments containing theophylline (THEO) within a hydroxypropyl cellulose (HPC) matrix were prepared using HME. 3DP tablets with different infill percentages and shell thickness were developed and evaluated to determine their drug content, floating behavior, dissolution, and physicochemical properties. The dissolution studies revealed a relationship between the infill percentage/shell thickness and the drug release behavior of the 3DP tablets. All the developed GRFTs possessed the ability to float for 10 h and exhibited zero-order release kinetics. The drug release could be described by the Peppas-Sahlin model, as a combination of Fickian diffusion and swelling mechanism. Drug crystallinity was found unaltered throughout the process. 3DP coupled with HME, could be an effective blueprint to produce controlled-release GRFTs, providing the advantage of simplicity and versatility compared to the conventional methods.